Analisis Sistem Pengendalian Internal, Internal Audit, Dan Kesadaran Anti-Fraud Terhadap Pencegahan Fraud Pada Pemerintah Daerah Kabupaten Sleman - Salmaa Salsabiila; Zaenal Wafa (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze whether the internal control system, internal audit, and anti-fraud awareness in the Regional Government of Sleman Regency influence fraud prevention. The population in this study includes all Civil Servants and Non-Civil Servants in Regional Apparatus Organizations within the scope of the Sleman Regency Government in 2024. The sample consists of Civil Servants and Non-Civil Servants working in the Finance Division of the Regional Apparatus Organizations within the Sleman Regency Government. The data used in this study are primary data obtained through the distribution of questionnaires directly to the respondents. A total of 100 questionnaires were distributed, but only 87 responses could be processed. The analysis involved regression testing and hypothesis testing using the t-test. The results show that the internal control system does not influence fraud prevention. Internal audit has a partial influence on fraud prevention. Anti-fraud awareness does not have a partial influence on fraud prevention within the Sleman Regency Government.